2005
DOI: 10.1007/s11096-004-1737-y
|View full text |Cite
|
Sign up to set email alerts
|

Action Research: a valuable research technique for service delivery development

Abstract: The evaluation of healthcare practice and service delivery is fraught with difficulties. Service development and/or delivery occurs within socially dynamic settings which are in a continual state of change. Service development also often involves large elements of improvisation. The action research approach is useful for health service research, as it supports collaboration between researchers and practitioners, and not only allows but makes explicit that the action researcher has both roles within the setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The physician changed the prescription to gliclazide 40 mg bd and patient's problem was resolved TB tuberculosis, DM diabetes mellitus play the dual role of being a researcher and a practitioner [24]. This allows the researcher to become an insider and understand the system better [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physician changed the prescription to gliclazide 40 mg bd and patient's problem was resolved TB tuberculosis, DM diabetes mellitus play the dual role of being a researcher and a practitioner [24]. This allows the researcher to become an insider and understand the system better [24].…”
Section: Discussionmentioning
confidence: 99%
“…This allows the researcher to become an insider and understand the system better [24]. The drawback of the study was some of the identified pharmaceutical care needs could not be addressed when the researcher provided the service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Working as an action researcher [19][20][21] , and using reflective practice to devise the potential remit for the SMP post if established on a full time basis 3. Implementation of a confidential questionnaire survey 22 undertaken within the local health authority to obtain general practitioner, practice nurse and community pharmacist views on areas they would utilise the SMP 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Using a combination of qualitative and quantitative methods to complement data collection, the SMP role was examined in depth. Action Research 19,20 , a qualitative research technique with a focus on 'fact finding' 21,24 , enabled the investigation of what the role could comprise and to generate the hypothesis that the specialist pharmacist, working within the secondary care setting, can perform a useful function. Triangulation 25 of methodology, using quantitative and qualitative study methods, enabled further validation and reliability assessment.…”
Section: Introductionmentioning
confidence: 99%